2014
DOI: 10.1149/2.0481410jes
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Charge on the Deposition Rate of Particles with Metals

Abstract: The influence of ζ-potential on the electrodeposition of particles with metals was investigated by the codeposition of three different types of particles (BaSO 4 , CaF 2 and K 1.33 Mn 8 O 16 ) with three different metals (nickel, copper and zinc) from seven different, unsupported (binary) and well-supported plating solutions across the whole pH range. The surface charge of the particles in the plating solutions was modified by adding potential determining ions that are electrochemically silent. The surface cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…6). Hence, it can be concluded that the electrophoretic movement contributes to the codeposition of particles, as previously reported, 70 though it is not a fundamental factor for their entrapment. In fact, Fransaer et al 37 established that the electrophoretic force can be neglected when deposition takes place on a rotating disk electrode.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…6). Hence, it can be concluded that the electrophoretic movement contributes to the codeposition of particles, as previously reported, 70 though it is not a fundamental factor for their entrapment. In fact, Fransaer et al 37 established that the electrophoretic force can be neglected when deposition takes place on a rotating disk electrode.…”
Section: Resultssupporting
confidence: 74%
“…71 Moreover, Soccol et al found that the ζ-potential strongly influences the codeposition of brownian particles. 70 It is then clear that the relevance of this kind of interaction is different for each case.…”
Section: Resultsmentioning
confidence: 99%
“…When attached, they change the surface energy and diffusional properties of the electrode [30], and may lead to the growth of a film. Soccol et al [31] explain the deposition rate of particles as the product of their transport rate to the electrode times the sticking probability. Transport is governed by the stagnation point, electrophoretic force, gravity, buoyancy, and diffusiophoretic forces, whereas the incorporation probability depends on London-van der Waals forces, double layer, electrophoretic force, diffusiophoretic force, image force, and solvation.…”
Section: Introductionmentioning
confidence: 99%